Collagen sponge scaffolds containing growth factors for the functional regeneration of tracheal epithelium. (9th April 2019) - Nakamura, Ryosuke; Katsuno, Tatsuya; Kitamura, Morimasa; Yamashita, Masaru; Tsuji, Takuya; Suzuki, Ryo; Kishimoto, Yo; Suehiro, Atsushi; Tateya, Ichiro; Nakamura, Tatsuo; Omori, Koichi
Abstract: Tracheal epithelia have barrier and mucociliary clearance functions that prevent invasion of extraneous particles and infectious materials. Hence, following tracheal reconstructions, functional and morphological regeneration of epithelia is required to prevent respiratory declines and infectious diseases. Although growth factors (GFs) promote the regeneration of tracheal epithelial morphologies, it remains unclear whether tracheal grafts containing GFs are beneficial for regeneration of tracheal epithelial functions. Thus, we fabricated collagen sponge scaffolds containing insulin‐like GF‐1 (IGF‐1) and the basic fibroblast, hepatocyte, and epidermal GFs (bFGFs, HGFs, and EGFs, respectively), and we evaluated the effects of the grafts on the functional regeneration of tracheal epithelia. Partial tracheal defects were imposed surgically, and collagen sponges containing IGF‐1, bFGF, HGF, or EGF were then transplanted to defect sites. Subsequent immunofluorescence studies suggested that EGF and bFGF contribute to regular distributions of tight junction molecules, and tracer permeability assays suggested that EGF and bFGF promote regeneration of barrier function. Increased ciliogenesis was also observed using scanning electron microscopy in reconstructed regions treated with EGF‐ and bFGF‐supplemented collagen sponges. However, bFGF‐supplemented collagen sponges led to greater microsphere transport than did EGF‐supplemented sponges. The present data suggested that collagen sponge scaffold containing bFGF promotes functional regeneration of tracheal epithelial tissues.